SOSIALISASI DAN PROMOSI INDUSTRI PENGOLAHAN BAMBU PADA KELOMPOK KARANG TARUNA DESA WAWOOSU KECAMATAN KOLONO KABUPATEN KONAWE SELATAN - Nurtikawati, Nurtikawati; Marhini, La Ode; Saputri, Shinta Arjunita; Said, Taufiq; Samiel, Edi; Tunda, Amin (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2023)
Community Service Program with the title: "Socialization and Training on Bamboo Weaving Crafts for the Karang Taruna Group in the Wawoosu Village, Kolono Sub-District, South Konawe Regency" aims to enhance the knowledge and skills of the Karang Taruna group in making bamboo crafts as an effort to create new job opportunities, particularly in the utilization of bamboo as an economically valuable craft. To achieve this, the service team conducts both socialization and training activities for the Karang Taruna group by carrying out socialization about bamboo processing as a weaving craft in this era, followed by training activities to enhance their skills. This is done considering the limited knowledge and skills of the younger generation in utilizing natural resources and the lack of innovation in making bamboo weaving crafts at market value. This service activity is carried out directly at the service location, starting from the identification of problems, workshops related to problem findings, socialization, and promotion of the bamboo processing industri, followed by collaborative production of one of the bamboo processing products, namely bamboo curtains. This activity has received a positive response and has been attended by the Karang Taruna group from the beginning to the end of the program. The socialization activities are focused on increasing the knowledge of the Karang Taruna group in determining target markets, promoting products, and innovating unique product creations. To improve the community's skills, the service team provides training in the form of making unique bamboo curtains.